2019
DOI: 10.2302/kjm.2018-0007-oa
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Metabolic Syndrome and Lifestyle Characteristics by Business Type among Japanese Workers in Small- and Medium-sized Enterprises

Abstract: This cross-sectional study investigated the associations of business type with the prevalence of metabolic syndrome (MetS) and lifestyle characteristics among workers in small-and medium-sized enterprises. In total, data from 167,736 workers (114,746 men and 52,990 women) who participated in health checkups in 2013 were analyzed using multilevel logistic regression models. The odds ratios (ORs) of having MetS, defined based on the criteria of the joint interim statement, were significantly higher in employees … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Our results are consistent with those of a previous Japanese study. Hozawa et al showed that male workers in the transportation industry were more likely to have unhealthy lifestyles such as smoking, walking less, eating before bedtime, and skipping breakfast 28 ) . Furthermore, multivariable analysis in our study revealed a significant association between hypertension and diabetes with working in the transportation industry ( Tables 4 and 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with those of a previous Japanese study. Hozawa et al showed that male workers in the transportation industry were more likely to have unhealthy lifestyles such as smoking, walking less, eating before bedtime, and skipping breakfast 28 ) . Furthermore, multivariable analysis in our study revealed a significant association between hypertension and diabetes with working in the transportation industry ( Tables 4 and 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Workers of traditional retail markets, which are typical small businesses that provide retail services, are known to have a higher risk of MetS than workers of large enterprises [ 7 ]. It has been reported that 74.8% of workers from small enterprises and retail services are over 50 years old and that 81.3% of them work more than 10 h per day, with work hours ranging from 5 AM to 10 PM, while having a very low income [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%